DEVELOPMENT OF RURAL LANDSCAPE IN WIELKOPOLSKA IN REFERENCE TO METABOLISM OF AGROECOSYSTEMS - Mizgajski, Andrzej (My University, 2007)
The purpose of this paper is to show the main features of landscape development in a regional scale with reference to socio-economic conditions and the processes of energy and matter flow in agroecosystems. Four main phases of rural landscape development have been distinguished during which the dominant processes determining the functioning of agroecosystems changed. After the initial phase there was a period of spatial expansion of the rural landscape at the expense of natural forests; this phase was followed by the intensification of use through increased external feeding of agroecosystems in energy and matter, and currently the diversification of human influence on environmental systems is becoming increasingly noticeable. The social role of farmers is going to be of fundamental importance to the future of the rural landscape. It is necessary to stimulate their behaviour to make sure that they acquire knowledge, skills and motivation to protect natural environment and the landscape.
Keywords: history of landscape; energy and matter flow; environmental protection; rural areas